Аkmukhanova N.R., Kokocinski M., Bauyenova M.O., Bolatkhan K., Sadvakasova A.К., Zayadan B.K. Opportunities to use the consortium of higher aquatic plants and microalgae in the treatment of polluted aquatic ecosystems: University in Poznan, Poznan, Poland; al-Farabi Kazakh national university, Almaty, Kazakhstan (Eurasian Journal of Ecology, 2018)
One of the priorities of modern environmental research is the development of theoretical and practical aspects of bioremediation of water bodies, based on the use of natural mechanisms of self-purification and self-healing of water bodies, the effect of which is associated with the activities of higheraquatic plants (HAP) and microorganisms belonging to different types of cyanobacteria and microalgae.The practical significance of these objects for bioremediation and post-treatment of water bodies isdetermined by the uniqueness of their metabolic abilities (photosynthesis, respiration, a variety of carbon sources, the ability to absorb atmospheric nitrogen, etc.), high cumulative and destructive abilityagainst heavy metals and organic pollutants such as oil, petroleum products, phenols, etc. The aim ofthe research was to study the process of wastewater treatment from heavy metals by the consortium ofHAP and microalgae in industrial wastewater. It is shown that the use of the consortium of HAP andmicroalgae in wastewater treatment is very effective compared to their use in purification processes inmonoculture. It was found that the use of the consortium of HAP and microalgae improved water quality,and the effect of purification from pollutants on some indicators was more than 95-100 %.Key words: higher aquatic plants, microalgae, consortium, bioremediation.